The Methuen Drama guide to contemporary Irish playwrights - Middeke, Martin; Schnierer, Peter Paul (Bloomsbury Publishing, 2018)
This is an authoritative single-volume guide to the work of 25 Irish playwrights from the 1960s to the present written by a team of 25 eminent scholars from Ireland, the USA, Britain, and Germany
Includes bibliographical references and index
Previously issued in print: London: Methuen Drama, 2010. Digital resource published 2018
Zielgruppe - Audience: Specialized